Pengaruh Investment Opportunity Set, Operating Cash Flow, dan Solvency terhadap Financial Distress Dimoderasi Kepemilikan Manajerial - Ayu Permata Sari; Nera Marinda Machdar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Financial distress is a situation where a company faces serious financial problems that can threaten the continuity and stability of the company. This can affect the company's reputation, credibility and public trust, and even lead to bankruptcy. Therefore, effective management, prudent financial planning, and monitoring the state of the company are very important to prevent or overcome financial distress. The purpose of this study is to determine and analyse the theory that explains the effect of investment opportunity set, operating cash flow, and solvency on financial distress moderated by managerial ownership. This study uses qualitative descriptive method for literature research. The results of this study indicate that the variables of investment opportunity set, operating cash flow, and solvency affect financial distress. Managerial ownership is able to moderate the investment opportunity set, operating cash flow, and solvency on financial distress.